Numerical Simulation on Impact Test of CFRP Strengthened Reinforced Concrete Beams - Qingfeng, He; Jiang, Li; Leiyang, Yue; Jiawei, Mao (Frontiers in Materials, 2020)
In order to study the dynamic performance of reinforced concrete beams before and after CFRP reinforcement under different impact conditions, the finite element analysis software ANSYS/LSDYNA was used to simulate the impact test of five ordinary RC beams and five strengthened beams. The impact speed and impact weight of the drop hammer are mainly changed during the simulation, and the stress distribution, crack development and failure morphology, and CFRP resistance contribution of the specimen were analyzed. The simulation results show that CFRP can alleviate the high stress in the impact transient concrete, reduce the deformation of the beam body, limit the crack development, and provide a certain impact resistance. The increase of the impact height has a more significant effect on the transient response of the component. CFRP can effectively restrain the deformation under different impact weight conditions.